Measuring inflammation in patients with allergic rhinitis using different biomarkers - Hamad, Sherko Omer; Janson, Christer; Rahman, Heshu Sulaiman; Issa, Sulaf Mousa; Othman, Hemn Hassan; Tahir, Dara Abdulrazaq; Amin, Kawa (Sulaimani Journal for Pure and Applied Sciences, 2020)
Allergic rhinitis is an inflammatory disease affecting the mucosal lining of the nose of individuals of all ages. The allergen in the air involves‏ attaching by Immunoglobulin E that causes the release of inflammatory chemicals from mast cells. This study aimed to measure the serum level of biomarkers and to determine the correlation between them in mediating activate cell in patients with AR.In this study, blood samples were taken from 88 AR patients and 88 healthy controls (HC) Symptom score was measured using the SNOT-22 questionnaire and blood sample was analyzed for eosinophil counts (B-Eos) using optical flow cytometry, IgE by electrochemiluminescence immunoassay, as well as eosinophilic cationic protein, anti-alpha smooth muscle actin (anti-SMA), cyclooxygenase- 2 (COX-2R), phosphatase and tensin (PTEN) homolog and Tryptase Alpha/Beta 1 (TPSABI) by ELISA. B-Eos, IgE, ECP, anti-SMA, and symptom scores were significantly higher in AR patients than in HC. As a result, we found that there was correlation between B-Eos and ECP (r = 0.66, p = 0.001). There was also a correlation between IgE and symptom score (r=0.64, p=0.01). COX-2 also correlated with symptoms score (r = 0.52, p = 0.04). There was a positive correlation between phosphatase and tensin homolog and TPSAB1 (r = 0.76, p<0.001) and PTEN and ECP (r = 0.53, p = 0.03). In conclusion, we realized that in allergic rhinitis, the airway inflammation was characterized by high numbers of eosinophil, IgE, ECP and anti-SMA. B- Eos, IgE and COX-2 were related to symptom scores. The study highlights the importance of systemic inflammation in AR.
Keywords: Allergic rhinitis; cross-section study; immune system; serum biomarkers